Preparation of Standard Unit Price of Goods and Services (SHBJ) in East Java Provincial Government - Kariyoto Kariyoto (Institute of Research and Community Service, University of Brawijaya)
Forming standard unit price of goods and services is an activity survey to collect data required in Local Government and State requirements. Goods and services are under control of the Department or institution by the local government. Standards Unit Price of Goods and Services assist in preparing the Budget Requirement Plan, the regional work units and the Budget Implementation Document. Standards Unit Price of Goods and Services is to guide the preparation of the Budget Requirement Plan, the regional work units and the Budget Implementation Document work unit East Java Provincial Government. Data and information collection techniques are done by conducting market surveys, through distributors and the highest retail prices in stores and markets. The data types of goods and price list are based on the standard of the goods provided the provider distributors and stores. The interviews involves distributors, sellers to consumers. It also involves the data from Related Work Unit in cooperation with the Government of East Java to obtain secondary data. Conclusions are based on the description and presentation of data on survey results as the preparation of this Book Standard Unit Price of Goods and Services. This book is a guide to the standard unit price of goods and services that are indispensable in East Java Provincial Government work units.Keywords: standard unit price, goods and services, the province of East Java